Analisis Nilai Moral dan Nilai Sosial dalam Novel "Selamat Tinggal" Karya Tere Liye serta Pemanfaatannya sebagai Bahan Ajar Sastra Indonesia Berbasis TPACK di SMA - Melisa, Melisa (Jurnal Artikula, 2024)
This study aims to describe the moral and social values in the novel “Selamat Tinggal”by Tere Liye and its utilization as a TPACK-based Indonesian literature teaching material in high school. This research was conducted based on a qualitative approach with a descriptive method that focuses on content analysis. The data and data sources in this study are in the form of texts, such as: words, pharases, sentences and conversations related to moral and social values. The instrument used in this study was the researcher himself with a theory validation test. Based on the description of the results of the analysis of the novel “Selamat Tinggal”by Tere Liye, it contains moral and social values, namely that by remembering god and carrying out his commandments, the heart can become calm and make life peaceful and get goodness. This research is recommended to be considered as a learning material for Indonesian language and literature to improve students’ ability to understand moral and social values in literary works, especially novels, and can improve literature teaching in schools.